2010
DOI: 10.2353/ajpath.2010.100220
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Sphingosine 1-Phosphate Receptors, S1P1 and S1P3, Sphingosine Kinase 1, and Extracellular Signal-Regulated Kinase-1/2 Is Associated with Development of Tamoxifen Resistance in Estrogen Receptor-Positive Breast Cancer Patients

Abstract: Various studies in cell lines have previously demonstrated that sphingosine kinase 1 (SK1) and extracellular signal-regulated kinase 1/2 (ERK-1/2) interact in an estrogen receptor (ER)-dependent manner to influence both breast cancer cell growth and migration. A cohort of 304 ER-positive breast cancer patients was used to investigate the prognostic significance of sphingosine 1-phosphate (S1P) receptors 1, 2, and 3 (ie, S1P 1 , S1P 2 , and S1P 3 ), SK1, and ERK-1/2 expression levels. Expression levels of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
155
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 23 publications
(51 reference statements)
15
155
0
1
Order By: Relevance
“…Besides, the study in 2008 also showed SPHK1 correlated with poor prognosis in ER‐negative breast cancer 34. Moreover, in 2010 Watson et al35 found that high expression of SPHK1 and ERK‐1/2 is associated with shorter recurrence time in ER positive patients. Besides, high level of S1PR1 and ERK1/2 or high expression of S1PR3 and ERK1/2 also indicated the association with shorter recurrence times.…”
Section: Discussionmentioning
confidence: 94%
“…Besides, the study in 2008 also showed SPHK1 correlated with poor prognosis in ER‐negative breast cancer 34. Moreover, in 2010 Watson et al35 found that high expression of SPHK1 and ERK‐1/2 is associated with shorter recurrence time in ER positive patients. Besides, high level of S1PR1 and ERK1/2 or high expression of S1PR3 and ERK1/2 also indicated the association with shorter recurrence times.…”
Section: Discussionmentioning
confidence: 94%
“…Similar observations were obtained using xenografted tumour samples in nude mice. SphK1 has been already shown to be upregulated in patients with breast cancer 43 , and its expression correlates with cancer progression and poor prognosis [43][44][45] . In addition, S1PR3 is the most highly expressed S1PR in breast cancer cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…High expression of S1P 1 or S1P 3 by ER + breast cancer cells correlated with poor prognosis and high S1P 1 expression induced decreased expression of pro-apoptotic markers ( 165,166 ). In ER Ϫ breast cancer cells, S1P 4 expression activated the ERK1/2 pathway and correlated with poor prognosis ( 167 ).…”
Section: Nervous Systemmentioning
confidence: 96%